Pengaruh Perilaku Pemimpin dan Kompensasi Terhadap Prestasi Kerja pada PT. Pelindo II (Persero) Cabang Pontianak - WARDHANA B3110901, STEFANUS HARRY CHANDRA (Jurnal Manajemen Update, 2015)
This study aimed to see are there the influence of leadership behavior and compensation against work performance at PT. Pelindo II (Persero) Branch Pontianak. The object of research is taken from container terminal employees of PT. Pelindo II (Persero) Branch Pontianak. The samples in this study were 130 samples. Data collection method used is to deploy questionnaires were processed using multiple linear regression analysis techniques. The results obtained in this study is that both variables together have a positive and significant influence on employee performance PT. Pelindo II (Persero) Branch Pontianak with result of F is 13,774 and R square is 20,8%, so rejected Ho and accepted Ha. Furthermore of the two variables is partially, leadership behavior variable (X1) has significant influence on work performance (Y) with tables of t is 4,975 so that rejected Ho and accepted Ha, while for the compensation variable (X2) partially don’t has significant influence on work performance (Y) with tables of t is 0,285 so that accepted Ho and rejected Ha. This case can happen because compensation which accepted is fixed so that less influence increasing from work performance. Advice can be given by the researchers is leaders must be able to approach both relationship behavior and task behavior which better because that variable proved significant influance. Meanwhile, the compensation which had obtained must defended in order to work performance didn’t decline. Keywords: leadership behavior, compensation and work performance.